Acid reduction and Helicobacter pylori treatment in pyloric stenosis: A prospective study - Sadık YILDIRIM,; Levent ERDEM,; Hakan M. KÖKSAL,; Adil BAYKAN,; Halil İ. MEDE,; Ömer KURT, (Turkish Journal of Gastroenterology, 2019)
-